EFEKTIVITAS MEDIA EDUKASI BOOKLET TERHADAP PENINGKATAN PENGETAHUAN, SIKAP, DAN POLA ASUH IBU BALITA STUNTING DI WILAYAH KERJA UPTD PUSKESMAS TABUKAN TAHUN 2025 - Ni’mah, Hayatun; Isnaniah, Isnaniah; Zakiah, Zakiah; Hipni, Rubiati (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: Stunting remains a complex child health issue in Indonesia, partly caused by limited maternal knowledge, attitudes, and parenting practices. Educational efforts through booklet media are considered effective in improving mothers understanding of stunting prevention. Objective: To determine the effectiveness of educational booklet media on the knowledge, attitudes, and parenting practices of mothers of stunted toddlers in the working area of UPTD Puskesmas Tabukan in 2025. Methods: The study employed a pre-experimental design with a one group pretest-posttest approach. The sampling technique used was quota sampling, with a minimum of 30 mothers of stunted toddlers. Data were analyzed using the Wilcoxon Signed Rank Test. Results: There was a significant improvement after the intervention: good knowledge increased from 46.7% to 73.3%, positive attitudes from 56.7% to 96.7%, and proper parenting from 66.7% to 90%. The mean scores also increased: knowledge from 65.00 to 83.33; attitude from 66.65 to 86.01; and parenting from 29.16 to 32.5. The Wilcoxon Signed Rank Test showed a p-value of 0.000 (p < 0.05) for all variables, indicating a statistically significant difference before and after the intervention. Conclusion: The booklet is effective in increasing knowledge, fostering positive attitudes, and improving parenting practices of mothers with stunted toddlers. The booklet can be used as an educational medium in health promotion programs for stunting prevention.